Experimental Study on Fire Resistance of Concrete Beams Made with Iron Tailings Sand - Yunlong Zhou; Zhinian Yang; Zhiguo You; Xingguo Wang; Kaijiang Chen; Boyu Guo; Kai Wu (Buildings, 2022)
In order to measure the effect of iron tailings sand replacing natural sand on the fire resistance of concrete beams, five full-scale iron tailings sand concrete (ITSC) beams and two natural sand concrete (NSC) beams were conducted to fire testing under dead load and rising temperature conditions. The section temperature field, mid-span displacement, failure form, and fire resistance limit of ITSC beams under fire were analyzed. The main influence factors included different ISTC strengths (C30 and C40) and constraints. The analysis results were compared with those of NSC beams. The results show that the complete replacement of natural sand with iron tailings sand had little influence on the temperature field of concrete and reinforcement in simply supported beams and continuous beams under fire. The fire endurance of the ITSC simply supported beams was similar to that of NSC simply supported beams. When exposed to fire, the higher the strength of the ITSC, the better the fire resistance of the beam. The fire endurance of continuous beams was higher than that of simply supported beams. On the basis of the analysis of the fire resistance performance, it was found that iron tailings sand can replace natural sand to formulate concrete beams.